Autocad 2008 for architecture - Jefferis, Alan. 4 0 16; 1964- Jones, Michael,;Jefferis, Tereasa; 5 (Australia ;;Clifton Park, NY : Thomson/Delmar Learning, 2008)
Presents techniques for using AutoCAD--a computer program for two- and three-dimensional drawing--for architecture, covering everything from the program's tools and displays to publishing drawings on the Internet, and includes chapter exercises and quizzes.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Data processing.;Computer-aided design.;Data processing.;Computer software. -- Architectural drawing;Architecture;Architectural drawing;Architecture; 20; 2